Temperature Dependence of the Activation Energy of Thin Films of Zinc Sulphide, Copper Phthalocyanine and Multi- layer Zinc Sulphide-Copper Phthalocyanine - Iype, Mercy; Varghese, Shaji; Mathew, E.J.; Menon, C.S. (Asian Journal of Chemistry, 2010)
Zinc sulphide (ZnS) thin films are prepared onto glass substrates by chemical bath deposition (CBD) technique. Thin films of copper phthalocyanine (CuPc) are also sublimed onto glass substrates in high vacuum at room temperature. Multi-layer ZnS-CuPc thin films are obtained from ZnS films grown on glass substrates by CBD technique and subsequently vaccum subliming CuPc onto them. These films are annealed in air at different temperatures. Electrical conductivity studies are made separately on ZnS, CuPc and multi-layer ZnS-CuPc thin films. Thermal activation energy of the as deposited and annealed samples are determined from the Arrhenius plot. It is found that the activation energy decreases with annealing temperature. This may be due to the reduction in trap sites during annealing.